Se você gostou, curta ou comente. Brand awareness e engajamento na #psicologia no Instagram - SANTOS, Thiago Filipe Linhares (2022)
In network societies, social media have redesigned relationships to a dynamic and borderless character. Hence, participation in social media has become a fundamental element for brands, whether personal or not. Through an adequate positioning, it is possible to generate rapprochement with potential clients, which includes the provision of services by psychologists. Thus, the understanding of how image built by a brand is perceived and interpreted by Instagram users can be assessed through engagement measurement efforts. In this regard, the present dissertation sought to answer the following research questions: how do internet users engage in psychology publications on Instagram? What are the main topics covered in these publications? Are there psychology professionals making use of #psicologia, since this is the key reference to this area in that social platform? How do these professionals position themselves? Data were obtained through web scrapping (data extraction) done through computational tools and collected from the scope delimited by the hashtag #psicologia. Textual data, likes, comments, and co-occurrence networks of users and hashtags were obtained. For the analysis of the results, Pierre Bourdieu’s Field Theory was used to understand Instagram as a social field, in addition to the concepts of brand awareness and personal brand to analyse data clusters and themes addressed in social media. The ethical implications that govern the professional promotion of psychologists, according to the norms and rules established by the Federal Council of Psychology were used to compare user’s positioning on this field. It was found that the use of #psicologia is triggered by users outside the hegemonic field of psychology, with postings achieving highest metrics associated with non-hegemonic elements (generalist groups and groups focused on well-being themes). In addition, the results pointed out that the presence of psychologists positioning themselves on this network using the researched hashtag is reduced, which allows its use by subjects initially external to the professional field.